Development of Portal Pintar Utilization Evaluation Dashboard (Case Study: BPS Province of Bengkulu) - Josaphat, Bony Parulian; Humaira, Rifka (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
BPS Statistics Province of Bengkulu (BPS Provinsi Bengkulu) plays a role insupporting statistical operations in Province of Bengkulu. As a vertical agency of StatisticsIndonesia (BPS), BPS Province of Bengkulu also holds an important role in providing statisticaldata at the regional level. Naturally, BPS Province of Bengkulu also requires an integratedsystem to facilitate all activities, such as providing easier and faster access to information for allemployees—both in reporting work progress and in monitoring the implementation of activitiessuch as agenda planning, facility usage, facility loan management, and cross-unit coordination.Portal Pintar is a portal used to facilitate the management of various activities in BPS Provinceof Bengkulu. By using Portal Pintar, users can access and manage various types of informationand documents, such as activity agendas, correspondence, and facility loan applications. BPSProvince of Bengkulu then produces periodic evaluations of Portal Pintar’s utilization, which aredistributed to all employees. However, the evaluations conducted are not yet visualizedautomatically and in real time, hence the need to develop a Portal Pintar Utilization EvaluationDashboard in which visualizations are generated automatically and connected to Portal Pintar’sAPI. Through the development of this dashboard, it is expected that the evaluation of PortalPintar’s utilization will become more integrated.